Athletic skin injuries - Basler, R. S. W.; Hunzeker, C. M.; Garcia, M. A.; Dexter, W. (The Physician and Sportsmedicine, 2004)
Because the skin is the athlete's first line of defense, it is exposed to friction and pressure in nearly every athletic setting. Whether applied acutely or chronically, friction and pressure often cause skin trauma, such as abrasions, chafing, calluses, blisters, talon noir (black heel), and acne mechanica. Sports medicine clinicians, who regularly see skin injuries, can speed healing by making a timely diagnosis, recommending effective treatment, and discussing prevention strategies.